2013
DOI: 10.1016/j.jchf.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

RAnoLazIne for the Treatment of Diastolic Heart Failure in Patients With Preserved Ejection Fraction

Abstract: Results of this proof-of-concept study revealed that ranolazine improved measures of hemodynamics but that there was no improvement in relaxation parameters. (Ranolazine in Diastolic Heart Failure [RALI-DHF]; NCT01163734).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 30 publications
0
94
0
3
Order By: Relevance
“…Furthermore, in a study of rats fed a high salt diet to induce hypertension, ranolazine therapy reduced oxidative stress and attenuated diastolic dysfunction (De Angelis, et al, 2016). Importantly, a 30-minute ranolazine infusion in patients with HFpEF reduced LVEDP in the RALI-DHF study (Maier, et al, 2013). In another study by Murray and Colombo, up to 70% of patients with HFrEF showed an improvement in EF when treated with ranolazine, compared to no improvement in the noradrenaline treatment arm (Murray & Colombo, 2014).…”
Section: Partial Fatty Acid Oxidation Inhibitionmentioning
confidence: 99%
“…Furthermore, in a study of rats fed a high salt diet to induce hypertension, ranolazine therapy reduced oxidative stress and attenuated diastolic dysfunction (De Angelis, et al, 2016). Importantly, a 30-minute ranolazine infusion in patients with HFpEF reduced LVEDP in the RALI-DHF study (Maier, et al, 2013). In another study by Murray and Colombo, up to 70% of patients with HFrEF showed an improvement in EF when treated with ranolazine, compared to no improvement in the noradrenaline treatment arm (Murray & Colombo, 2014).…”
Section: Partial Fatty Acid Oxidation Inhibitionmentioning
confidence: 99%
“…Проведенный анализ показал, что прием препарата в течение 13 дней привел к улучшению показателей гемодинамики, но при этом отсутствовали изменения параметров релаксации [24].…”
Section: результаты и обсуждениеunclassified
“…Nitroglycerin use also decreased in the treatment arm by one use per week vs. placebo ( P  < 0.02). In a recent, small proof‐of‐concept RCT, ranolazine was further shown to improve haemodynamics [with decreases in left ventricular end‐diastolic pressure ( P  = 0.04) and pulmonary capillary wedge pressure ( P  = 0.04) in patients with HFpEF (Maier et al ., 2013)].…”
Section: Metabolic Dysfunction In Heart Failurementioning
confidence: 99%